A Smart Switch to Connect and Disconnect Electrical Devices At Home by Using Internet - Sukanya Rani, A; Umamaheshwar, S (International Journal of Computer Sciences and Engineering, 2025)
This project presents the development of a firmware for a Smart Switch, which can control the on-off of any electrical device at home by using internet. The Smart Switch is connected to internet via Wi-Fi, through a computer, smartphone, tablet or any device with internet access. In order to perform this connection it is necessary to write the IP pre-programmed into the Smart Switch in a web browser (Internet Explorer, Chrome,Firefox, etc.) with the purpose to load the Smart Switch server, which will open a configuration page to write the data of the user’s network. Then, the user will select in automatic mode the network, the security type, and the user must have written a passphrase. Once these information is uploaded and saved, it is necessary to restart the Smart Switch in order to get access to internet, from which the user can control the Smart Switch simply sending a number one or a number zero to switch the electrical device, this process is done in principle via the internet.